MÎQÂT MAKÂNÎ JEMAAH HAJI INDONESIA MENURUT KEMENTERIAN AGAMA DAN ORGANISASI PERSATUAN ISLAM - Muhammat Nuri (Universitas Islam Negeri Jakarta, 2014)
Indonesian Hajj Mîqât Makânî According to the Ministry of Religious Affairs and the Persatuan Islam (PERSIS). Hajj is one of the worship that takes place every year. A Muslim is required to perform the pilgrimage only one time in his life when he was able. As the general character of fiqh, the hajj fiqh was not immune from the differences of opinion. One of the differences of opinion in the Hajj for pilgrims Indonesia is the difference in determining mîqât makânî. Two religious institutions, the Ministry of Religious Affairs and the Persatuan Islam (PERSIS) have different opinions on this.DOI: 10.15408/ajis.v14i1.1243